(untitled) (Journal of Nobel Medical College, 2023)
Background: Rational use of analgesic drugs is needed for immediate relief of pain. This study was conducted to find out the prescribing pattern of analgesics in the emergency department. Materials and Methods: A descriptive cross-sectional study among patients attending the emergency department of a tertiary care hospital from March 2022 to February 2023 after approval from the Institutional Review Committee. Demographic profile, indications for analgesics use, route, and frequency of administration were recorded based on the pre-structured questionnaires. Convenient sampling was done. Data were analyzed by using SPSS, version 20. Results: Prescription patterns of analgesics were analyzed in 325 patients. The mean age was 46.93 ± 17.79 years with a male predominance of 196 (60.6%). Orthopedic problems 99(30.5%) due to trauma were the most common indications followed by medical and surgical indications for analgesic use. Non-steroidal anti-inflammatory drugs were used in 46.6%, opioids in 26.8%, combinations in 23%, and antispasmodics in 3.6%. Commonly prescribed analgesic was ketorolac (27.4%), tramadol (19.7%), and diclofenac (11.4%). The most common combination was ketorolac and tramadol (14.5%). Paracetamol alone was used in 16 (4.9%). A prescription with a generic name was 149 (45.8%). Parenteral use accounted for 86.8%. Co-administration of gastroprotective drugs was used in 93.2%. A fixed-dose combination was used in 1.2%. Conclusion: Non-steroidal anti-inflammatory drugs are the commonly used analgesics for various indications, including acute pain and fever. The choice of analgesics and their prescription pattern varied depending on indications, medical history, and the presence of co-morbidities. Ketorolac and tramadol were the most commonly prescribed analgesics.